An investigation of implied volatility during financial crisis: evidence from Australian index options - Abdullah, Mimi Hafizah; Harun, Hanani Farhah (2014)
Volatility implied by an option pricing model is seen as the market participants’ assessment of volatility. Past studies documented that implied volatility based on an option pricing model is found to outperform the historical volatility in forecasting future realised volatility. Thus, this study examines the implied volatility smiles and term structures in the Australian S&P/ASX 200 index options from the year 2001 to 2010, which covers the global financial crisis in the mid-2007 until the end of 2008. The results show that the implied volatility rises significantly during the crisis period, which is three time the rate before crisis.